PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE PADA MATERI BENTUK ALJABAR KELAS VII - Lestari, Indah Fuji; R, Zubaidah; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract       This study aims to determine the effectiveness of the Think Pair Share (TPS) cooperative learning model on algebraic material at class VIIA SMP Negeri 6 Pontianak. The research method is qualitative research and research design is a pre-experimental design. The subjects of this study were 28 seventh grade students of Pontianak State Middle School. There are three aspects that are used to determine the effectiveness of cooperative learning models with TPS, such as the implementation of learning, student activities, and completeness of student learning outcomes. There are two techniques for collecting data, namely measurement and observation techniques. The tool used in this study is a test of student learning outcomes in the form of essays, of observation of the implementation of learning, and observation of  of student activity. Data were analyzed and found that the implementation of learning was categorized very well, student activities were obtained during the two meetings including the active group, but the standard test scores did not meet the requirements. So, the effectiveness of the cooperative learning model with think pair share (TPS) on algebraic material at class VIIA SMP Negeri 6 Pontianak Keywords: Effectiveness, Cooperative Learning Model with TPS, algebraic       expressions